LANGUAGE AND GENDER : ANALYSIS OF MARGARET THATCHER’S QUOTES - Utami Dewi (VISION, 2016)
Language style is the entity of a speaker. There are many factors that influence one’s language style, such as: gender, social status, educational background, etc. Both of men and women have their own characteristic and behavior in the society so it can make them become different in some aspect, especially in the way they use a language. It means gender influence one’s language style. Men and women have different role and status in the society. The way of their thought and then represent it into a language is also different. This article describes about analysis of Margaret Thatcher’s quotes. Most of Margaret Thatcher’s quotes shows that she uses more Men’s language than Women’s language. It means that women do not automatically use the feminin language. It depends on some factors.